Fundamentos para publicação de dados na Web - Corrales, Beatriz Rossi; Lóscio, Bernadette Farias; Guimarães, Caroline Burle dos Santos; Oliveira, Marcelo Iury de Sousa; Calegari, Newton Juniano (Comitê Gestor da Internet no Brasil, 2018)
64 p.